2009
DOI: 10.1111/j.1442-9071.2008.01891.x
|View full text |Cite
|
Sign up to set email alerts
|

Scanning laser polarimetry – a review

Abstract: Glaucoma is a leading cause of irreversible blindness worldwide. Retinal ganglion cells and their axons represent the selective target of the disease. When visual function is still intact on standard automated perimetry and optic disc appearance is suspicious, an early diagnosis may be supported by the identification of a retinal nerve fibre layer (RNFL) defect in the peripapillary area. At present days, computer-based, real-time imaging of the peripapillary RNFL is available through instruments of easy use an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The newest SLP version, the GDx ECC with enhanced corneal compensator13 25 reduces atypical retardation patterns (ARPs) measured by TSS 18 26 27. The ability of SLP to discriminate between healthy and glaucomatous eyes has been shown to decrease when ARPs are present 6 17 28. Moreover, ARPs are not necessarily stable over time,18 and can therefore either mask true progressing eyes (if ARP increases over time) or cause the GPA to detect false progression (if ARP decreases over time).…”
Section: Discussionmentioning
confidence: 99%
“…The newest SLP version, the GDx ECC with enhanced corneal compensator13 25 reduces atypical retardation patterns (ARPs) measured by TSS 18 26 27. The ability of SLP to discriminate between healthy and glaucomatous eyes has been shown to decrease when ARPs are present 6 17 28. Moreover, ARPs are not necessarily stable over time,18 and can therefore either mask true progressing eyes (if ARP increases over time) or cause the GPA to detect false progression (if ARP decreases over time).…”
Section: Discussionmentioning
confidence: 99%
“…[1, 2] During the past decade, several objective, quantitative methods have been introduced to assess these structural changes in the optic disc and the retinal nerve fiber layer. These include red-free fundus photography, [3, 4] stereo photography, [5] scanning laser polarimetry, [6] confocal scanning laser ophthalmoscopy (Heidelberg retinal tomography: HRT), and optical coherence tomography (OCT) [2, 79]. Measurement parameters of optic disc cupping have shown that it is significantly associated with glaucoma severity and that, interestingly, cupping precedes visual field loss.…”
Section: Introductionmentioning
confidence: 99%
“…GDx is known to be useful in detecting progressive RNFL thinning in primary open angle glaucoma as highlighted by Grewall et al [31], Reus et al [32], Toth et al [33], and summarised by Da Pozzo et al in their review of SLP [34]. Similarly, previous findings have reported that GDx is able to highlight superior and inferior RNFL defects 16 weeks after APAC [35].…”
Section: Gdx Evidence Of Damagementioning
confidence: 74%